PENINGKATAN KESADARAN DAN KEBERSIHAN LINGKUNGAN DENGAN PEMANFAATAN BANK SAMPAH DI RT 50 KELURAHAN MANGGAR DI BALIKPAPAN - Ariani, Misna; Tamara, Dwinda; Khudin Anam, Sholih; Hendrawan, Yudi (Fakultas Ekonomi Universitas Balikpapan, 2024)
Every individual needs to have awareness to keep the surrounding environment clean. This can be done by not littering, reducing the use of dangerous chemicals, and supporting greening and pollution control programs carried out by the government. Environmental cleanliness includes waste management, greening, pollution control, and maintaining natural beauty. In maintaining a clean environment, the active role of each individual is very important. Therefore, let's increase our awareness and role in maintaining the cleanliness of the environment around us in order to create a clean, healthy and beautiful environment.